POTENSI SEKTOR PERTANIAN DI JAWA TENGAH (THE AGRICULTURE SECTOR POTENTIALS IN CENTRAL JAVA PROVINCE) - Sumastuti, Efriyani (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2010)
The study analyses: 1) the agriculture sector income distribution at district and city levels in Central Java Province; 2) agriculture sector potentials at district and city levels in Central Java Province. The study utilizes time series data from 2005 to 2009 (five years).The result shows that there is a fair income distribution in agriculture sector among the district and city levels in Central Java, revealed by the Williamson index of less than 0.05. Amongst the 29 districts in Central Java, 65% (19 districts) have promising potentials in agriculture sector.